'Terrible Purity': Peter Singer, Harriet McBryde Johnson, and the Moral Significance of the Particular. Issue 4 (7th March 2017) - HOPWOOD, MARK
ABSTRACT: In her account of a debate held at Princeton University between herself and Peter Singer, the lawyer and disability rights activist Harriet McBryde Johnson criticizes the 'terrible purity of Singer's vision'. Although she certainly disagrees with the substance of Singer's arguments concerning disability and infanticide, this remark is best understood as a critique of their form. In this paper, I attempt to make sense of this critique. I argue that Singer's characteristic mode of argument, with its appeal to a universal, neutral point of view, makes it impossible for McBryde Johnson to give voice to her particular experience and thus obscures her humanity. In order to clarify the positive contribution that an appeal to particular experience may make to moral reasoning, I draw a parallel with the transformative effects of the experience of beauty, arguing that McBryde Johnson's writing ought to be regarded as both morally and philosophically instructive.